Evidence for “Whole Family Approach” in accelerating uptake of COVID-19 and routine immunizations among integrated primary health services in Nigeria - Offor, Chika; Ade-Banjo, Olympus; Nwankwo, Chika; Nwaononiwu, Grace; Adukwu, Faith; Egharevba, Bibianna; Owoyemi, Joshua; Odo, Chibuike; Olatunji, Marvellous (Frontiers in Health Services, 2023)
The Family family is the simplest unit which possesses the strongest bond in society. The bond and proximity that exist both within and across neighboring families, according to our research, can be instrumental to shaping a new kind of health promotion strategy that can transform health behaviors in communities. The Whole Family Approach (WFA) is a government-sanctioned approach to ramp up uptake of COVID-19 vaccines in Nigeria. The approach entails leveraging the high family-based demand for some primary health services such as malaria, diabetes, hypertension and reproductive services, to generate demand for COVID-19 and routine immunizations. However, since the announcement in 2021, there has not been available any available evidence to show the impact of the approach on COVID-19 vaccines uptake though global literature generally favors family-centered health approaches. This study tests the effectiveness of the approach in increasing the utilization of target services in a Nigerian community and further provides a theoretical framework for the strategy. This study thus provides a theoretical framework and tests the efficacy of the approach in increasing utilization of target services in a Nigerian community. Two primary healthcare facilities were selected in two communities located in Abuja in a quasi-experimental design. After a small-sample landscape assessment of the communities and the facilities, family-targeting health promotion activities were facilitated in the intervention community (integrated health education by trained community health influencers) and facility (opportunistic health promotion through in-facility referrals) for a period of one month. Anonymized service utilization data was were acquired from both facilities over a period of for a span of four months to analyze their respective month-by-month service utilization trends. Time trend analysis was conducted which revealed that WFA significantly increased service utilization (N=5870; p <0.001, α=0.01, 99% CI) across all the package services provided at the intervention facility. A supplementary Pearson’s correlation analysis further presented a positive relationship (r = 0.432 - 0.996) among the services which must have favored the result. It can, therefore, be concluded that the ‘Whole Family Approach’ of health promotion is efficacious in accelerating uptake of priority health services such as COVID-19 and routine immunizations.